Implementation of Port Call Synchronisation A case study of the Energy port in Gothenburg - Eskelinen, Martin (My University, 2018)
The maritime industry has during the last decade experienced an increased pressure from regulations and legislators to achieve a more energy efficient operation and reduce the emissions from ships. One possible way to reduce the emissions from ships is to arrive under the just-in-time principle and minimize the time spent at anchor. With the digitalisation leap in the maritime industry hopes the research project Sea Traffic Management and activity of Port Call Collaboration decision making make it possible. The aim of the thesis is to identify possible barriers for just-in-time arrivals among stakeholders in the Energy port in Gothenburg. A qualitative case study was conducted and six important stakeholders was interviewed regarding their business and view about just-in-time arrivals. From the literature was it found that ports are a very complex organisations and several different ownership models can exist, all with different missions and vision's. The literature also showed that transportation of oil products comes with different commercial aspects and risk for the stakeholders, depending on under what type of contract the goods is transported. From the interviews were this theory confirmed as possible barriers for allowing ships to arrive under the just-in-time principle. The main findings were that the port regulation and the shipping contracts hinders the ships to adjust the speed. However, during the research project was it also discovered that some of the stakeholders have developed own private contracts which allows the ship to adjust the speed if the berth is occupied. So, the maritime industry has implemented some actions to increase the energy efficiency and reduce the emission's.
Keywords: Transportteknik och logistik; Marin teknik; Hållbar utveckling; Transport; Transport Systems and Logistics; Marine Engineering; Sustainable Development; Transport